Validitas Permainan Edukasi Kahoot sebagai Alat Penilaian Pembelajaran bagi Calon Mahasiswa Program Studi Biologi - Nana Citrawati Lestari; Rezky Nefianthi; Rabiatul Adawiyah (Postgraduate, University of Mataram, 2025)
The rapid development of technology today requires development in the field of learning media in order to integrate technology in its process. One of strategy that can be used is integrating the technology as assessment tools. In this research, the platform that used is Kahoot. The objective of this research was to determine the validity products as assessment tool. This research used a modified 4D development model that only implemented till expert validation. Based on the expert validity test shows in terms of content/material aspect the product obtains 93.75% score with very valid criteria, then 97.50% score with very valid criteria also in media aspect, and 98.75% score with very valid criteria in language aspect. Based on this expert validity test, the product obtained overall validity score with a high percentage with a 96.67% value which meets the very good validity criteria. This study shows that the integration of technology can be combined as an assessment tool for prospective biology teacher students. This study is still limited to the validity test only, then this validated product can be used for further research to measure the level of effectiveness and practicality of its use.